The Impact of Proposed Prices on the Public Transport Providers and Passengers for Integrated Transport System in Kosice Region - Bibiana Poliakova; Jozef Stoklosa (Communications - Scientific letters of the University of Zilina, 2016)
The article deals with the price construction for integrated transport system as the key part of integration because it has the impact on the involved public transport providers and passengers, but also for the third very important part – the self-government regions or cities as the orders of public transport services. The data in this article are used for integrated transport system in Kosice region in Slovakia where the process of integration is in the preparing phase.